Hypertensive crisis in modern guidelines: how to avoid mistakes in diagnosis and treatment. Based on the materials of the XXVI Russian National «Human and Medicine» Congress and the III Cardiology Summit - Yu. V. Evsyutina (SINAPS LLC, 2019)
The prevalence of hypertension is about 40 % according to Russian and world statistics. Approximately 1-2 % of patients with hypertension have high blood pressure throughout their lives, which requires urgent or emergency care. Hypertensive crisis is an acute condition caused by a sudden increase in blood pressure to individually high values, accompanied by clinical symptoms and requiring a controlled reduction to prevent target organ damage. According to the severity of clinical symptoms, hypertensive crisis is divided into uncomplicated and complicated. Typical signs of hypertensive crisis include malignant hypertension, severe hypertension associated with other clinical conditions, a sudden increase in blood pressure due to pheochromocytoma associated with organ damage, severe hypertension during pregnancy or preeclampsia. Hypertensive crisis is associated with various acute conditions, most often stroke (ischemic and hemorrhagic), acute cardiogenic pulmonary edema, acute heart failure, acute coronary syndrome, acute kidney injury, acute aortic dissection and eclampsia. The main goals of the treatment of hypertensive crisis are relief of the crisis, post-crisis stabilization, and prevention of repeated hypertensive crises. In patients with an uncomplicated hypertensive crisis, a decrease in mean blood pressure by 10 % during the first hour and by another 15 % during the next 2-3 hours is recommended. Therapy of complicated hypertensive crisis consists in the mandatory use of intravenous drugs with a predictable and controlled effect. The prognosis in patients with a hypertensive crisis, especially complicated one, is not favorable due to the high risk of short-term and long-term mortality. Patients who have undergone a hypertensive crisis require long-term follow-up.